1963
DOI: 10.1103/physrev.130.2302
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance ofXe129in Natural Xenon

Abstract: Nuclear magnetic resonance studies of natural xenon have been continued using fluid samples with improved purity. The Xe 129 spin-lattice relaxation time in the gas was found to be inversely proportional to the density: 1/7*1 = (5.0db0.5)X10 -6 p, where 7i is in sec and p in amagats. For the liquid in equilibrium with its vapor, the relaxation time throughout the temperature range 0° to -72°C is 1000±200 sec. In both the gas and the liquid the paramagnetic shift in the resonant value of the local field H at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 10 publications
6
34
0
Order By: Relevance
“…The main relaxation mechanism at high densities was confirmed to be spinrotation, as identified by the older studies (Streever andCarr 1961, Hunt andCarr 1963). For lower pressures, which can only be efficiently investigated using hyperpolarized xenon, they suggested that wall effects become dominant below 3 amagat.…”
Section: Relaxation Timesmentioning
confidence: 71%
See 2 more Smart Citations
“…The main relaxation mechanism at high densities was confirmed to be spinrotation, as identified by the older studies (Streever andCarr 1961, Hunt andCarr 1963). For lower pressures, which can only be efficiently investigated using hyperpolarized xenon, they suggested that wall effects become dominant below 3 amagat.…”
Section: Relaxation Timesmentioning
confidence: 71%
“…The influence of pressure and temperature on the chemical shift in gas, liquid and solid, as well as the underlying mechanisms have been studied. Streever and Carr (1961) and then Hunt and Carr (1963) studied the range of chemical shifts and longitudinal relaxation rates in gaseous and liquid xenon. Their observations showed that the chemical shift is accurately proportional to density over a range extending from rarefied gases well into the liquid phase, and determined the proportionality constant to be 0.422 ppm (the density being expressed in amagat).…”
Section: Chemical Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…This enhancement factor represents a loss of almost two orders of magnitude compared to the 129Xe polarization typically prepared by the optical pumping apparatus. It is likely that paramagnetic impurities in the metal valves and tubing were responsible for this loss in polarizatio~, because the T 1 relaxation times of xenon in the solid, liquid, and gas phases are extremely long, and no significant loss of polarization is suffered during transitions between phases [58,144,162,163]. Furthermore, once the supercritical state was achieved, the 129Xe polarization was observed to last for hundreds of seconds.…”
Section: Resultsmentioning
confidence: 96%
“…The corresponding Hamiltonian is given by c K (r)K · N, with coupling strength c K (r) between a nuclear spin K and the rotational angular momentum N of a pair of xenon atoms separated by a distance r [17]. In the gas and liquid phases, the rotational angular momentum N of the pair is provided by a colliding pair of Xe atoms-transient and/or persistent (van der Waals) dimers [6,[18][19][20]. In the solid phase, the orbital angular momentum of a neighboring Xe pair comes from the phonon bath, which can be analyzed to determine the ex- * mlimes@princeton.edu Xe T1 data from this work shown plotted vs. temperature for both naturally abundant ice and snow, as well as comparable data from Refs.…”
Section: Introductionmentioning
confidence: 99%